2020
DOI: 10.1038/s41598-020-68711-x
|View full text |Cite
|
Sign up to set email alerts
|

Passive training with upper extremity exoskeleton robot affects proprioceptive acuity and performance of motor learning

Abstract: Sports trainers often grasp and move trainees' limbs to give instructions on desired movements, and a merit of this passive training is the transferring of instructions via proprioceptive information. However, it remains unclear how passive training affects the proprioceptive system and improves learning. This study examined changes in proprioceptive acuity due to passive training to understand the underlying mechanisms of upper extremity training. Participants passively learned a trajectory of elbow-joint mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…Several forms of somatosensory intervention such as passive, repetitive cutaneous stimulation [ 10 , 11 ], passive limb movement training [ 12 ], repeated somatosensory discrimination practice and active sensorimotor training with augmented somatosensory feedback [ 7 , 13 , 14 , 15 ] have been proposed to aid recovery of proprioceptive function and motor function after stroke. Proprioceptive improvements observed after proprioceptive training interventions correlated with improvement of untrained motor performance in healthy young adults [ 16 , 17 ]. This further supports the rationale to implement proprioceptive-motor training for people with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Several forms of somatosensory intervention such as passive, repetitive cutaneous stimulation [ 10 , 11 ], passive limb movement training [ 12 ], repeated somatosensory discrimination practice and active sensorimotor training with augmented somatosensory feedback [ 7 , 13 , 14 , 15 ] have been proposed to aid recovery of proprioceptive function and motor function after stroke. Proprioceptive improvements observed after proprioceptive training interventions correlated with improvement of untrained motor performance in healthy young adults [ 16 , 17 ]. This further supports the rationale to implement proprioceptive-motor training for people with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In passive training, the patient is fully relaxed, and movements are fully assisted. This type of training reduces joint stiffness, edema [25] and improves proprioceptive acuity [26]. Active training is a crucial ingredient for recovery following neurological rehabilitation [27], [28], where the patient performs all movements voluntarily to complete therapy tasks; when a therapist or a robot provides some external assistance, this is referred to as active-assisted training.…”
Section: Introductionmentioning
confidence: 99%
“…The present task consists of a repetition of sequential finger movements, in which afferent sensory feedback derived from a keystroke is used to correct the subsequent movements for ensuring the spatiotemporal accuracy of those movements 8 . Several studies reported improvement of proprioceptive acuity through repetition of passive movements generated by a robot 30,31 . This may reduce the accuracy demand of the movements, and thereby allow for increasing the maximum rate of the repetitive finger movements.…”
Section: Discussionmentioning
confidence: 99%